2008
DOI: 10.1111/j.1469-7610.2007.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from adolescent deliberate self‐poisoning to early adult outcomes: a six‐year follow‐up

Abstract: Results 2060 unique articles were screened of which 28 (from 24 studies with 2 88 264 participants) were included. We statistically pooled information from 19 studies, showing that males with high intensity OPA had a higher risk of early mortality than those with light intensity OPA (HR [95% CI]: 1.24 [1.03 1.49). Such an association was not observed for females (0.88 [0.75 1.03]). Conclusion These findings support the PA health paradox, with levels of high intensity OPA being associated with ill-health (for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Additionally, studies have found hopelessness to be a stronger long-term predictor of repeat suicide attempts among previous attempters than depression (e.g., Groholt, Ekeberg, & Haldorsen, 2006). However, a study by Aglan and colleagues (2008) found that the long-term presence of major depression predicted deliberate self-harm over a 6-year period better than hopelessness within a sample of self-poisoning adolescents. Some studies focusing on high-risk psychiatric inpatient samples have found depression, but not hopelessness, to be a predictor of suicidal ideation, but neither depression nor hopelessness to be a predictor of suicidal behavior (Links et al, 2012; Prinstein et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, studies have found hopelessness to be a stronger long-term predictor of repeat suicide attempts among previous attempters than depression (e.g., Groholt, Ekeberg, & Haldorsen, 2006). However, a study by Aglan and colleagues (2008) found that the long-term presence of major depression predicted deliberate self-harm over a 6-year period better than hopelessness within a sample of self-poisoning adolescents. Some studies focusing on high-risk psychiatric inpatient samples have found depression, but not hopelessness, to be a predictor of suicidal ideation, but neither depression nor hopelessness to be a predictor of suicidal behavior (Links et al, 2012; Prinstein et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…2003), hopelessness, persistent depression (Brinkman et al . 2000; Aglan et al . 2008), suicidal thoughts, family dysfunction, dysthymia (King et al .…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of cognitive findings from the present study to earlier reports involving adolescents who were treated with index ECT alone, but not C-ECT or M-ECT, finds improved cognitive functions among the present group. 6,7 For instance, Ghaziuddin et al 6 studied 16 hospitalized adolescents with a mood disorder (13 girls, 3 boys; mean [SD] age, 15.9 [1.6] years; unipolar depression, 14; bipolar depression, 2) who were treated with mean (SD) number of treatments, 10.8 (2). 6,7,23 Psychotropic medications were withdrawn during the index course, which is necessary to minimize adverse effects during ECT and is consistent with the guidelines of the AACAP.…”
Section: Discussionmentioning
confidence: 99%